2020
DOI: 10.1002/csr.1917
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable development: Predictors of green consumerism in Slovenia

Abstract: Motivated by the growing worldwide concern for sustainable development, in this study, we explore the antecedents of green consumerism in an economy driven by environmental sustainability concerns. Drawing on a survey of 705 Slovenian consumers, we find that consumers' environmental commitment, perception of eco‐products, and perception of barriers to be green all positively affect the green purchase intention, which in turn positively and significantly affects consumers' purchase of eco‐products. The findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 73 publications
(160 reference statements)
2
28
0
Order By: Relevance
“…Although the correlations were weak or modest at best, our results build on previous findings [21,23,[25][26][27][28][34][35][36] and show that knowledge, attitudes toward the environment and bio-based ingredients, past green purchasing behavior, and intention to buy green and lignin skincare are all positively related. However, contrary to our predictions, health consciousness had the weakest associations with sustainable purchasing behavior and intention to purchase and a non-significant relationship with knowledge and willingness to buy lignin-based sunscreens, suggesting that consumers may not perceive lignin-based sunscreens and other bio-based skincare products as healthier choices for them [31,32].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Although the correlations were weak or modest at best, our results build on previous findings [21,23,[25][26][27][28][34][35][36] and show that knowledge, attitudes toward the environment and bio-based ingredients, past green purchasing behavior, and intention to buy green and lignin skincare are all positively related. However, contrary to our predictions, health consciousness had the weakest associations with sustainable purchasing behavior and intention to purchase and a non-significant relationship with knowledge and willingness to buy lignin-based sunscreens, suggesting that consumers may not perceive lignin-based sunscreens and other bio-based skincare products as healthier choices for them [31,32].…”
Section: Discussionsupporting
confidence: 84%
“…Furthermore, an extensive review on green purchasing behavior found that knowledge about environmental issues and eco-products is the most studied variable and one of the most influential factors affecting purchase intention and behavior, both directly and indirectly, by influencing consumers' attitudes [31,[34][35][36]. A recent study showed that while there were no differences between males and females in purchase intention and familiarity with environmental issues, female consumers showed more concern for the environment and were more familiar with eco-products [35].…”
Section: Attitude Knowledge and Behavior In Relation To Green Skincare Productsmentioning
confidence: 99%
“…They have also found that the motives to adopt green behavior are related more to the personal benefits that can be acquired rather than the belief of protecting the environment itself. In Slovenia, women are more committed toward the environment and are more ready to buy green products than men (Hojnik et al, 2020).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…People with strong environmental values are more likely to consider that environmental and ecological conservation is ethical and just (Laroche et al, 2001). Environmental values can induce individuals to engage in consumption behaviors with lower environmental burden, because environmental benefits and sustainable development conform to their ethical beliefs (Hojnik et al, 2020). High environmental concerns have significant and positive effects on sustainable consumption behaviors (Thøgersen & Ölander, 2003).…”
Section: Research Model and Hypothesesmentioning
confidence: 99%